Research Progress of Food Components Affecting the Gluten Network and the Processing Quality of Dough - Xueyan ZHANG; Jingke LIU; Pengliang LI; Wei ZHAO; Xiaodi ZHANG; Huan YANG; Qinghai SHENG; Aixia ZHANG (Shipin gongye ke-ji)
Mixing wheat flour and water to form dough is an important link of flour processing, which will directly affect the quality of processed products. Dough is a dispersed system formed by a variety of food components through complex interactions, and its stability is affected by the structure of the gluten network. It is reviewed the relationship between gluten-forming wheat protein components, gluten network and the processing quality of dough. The gluten network formed by gluten and gliadin through disulfide bonds is an important factor which affecting the viscoelasticity and stability of dough. Starch acts as an important filling material in the gluten network and maintains the integrity of the dough morphology. Lipids can improve the softness of the dough. Sugar can enhance the shear resistance of the dough, delay the ageing of the products, and improve product quality. Other food components, such as phenols, enzymes, inorganic salts and water, may also affect on the formation of gluten and improve the rheological properties of dough. In this paper, the influence of food components on gluten network and the processing quality of dough are expounded in order to provide theoretical basis and research ideas for improving the adaptability of dough processing and product quality in flour product processing.